OUTWARD CURVATURE RUNNER WITH AIR VENTS FOR DIE CASTED TEST PIECE BASED ON MANUFACTURABLE MOLD DESIGN - JASMINE, JENDIA (Universiti Malaysia Sarawak, (UNIMAS), 2019)
Die casting is a manufacturing process used to produce complex and precise products where molten material is injected into the mold cavity at a very high speed and pressure. Metal injection molding manufacturing is gradually increasing due to the demand for lightweight and sustainable material. Magnesium has several unique physical properties that are comparable with Aluminum metal. In this research, the objective is to study the effect of modification on runner and installation of air vents in reducing investigated defects location. The design of the cavity in this project is a ‘test piece’, an inspection instrument. Design modeling and the relevant parameter is input into ANSYS software for numerical simulation. Novelty runner and gate design (Outward curvature runner with air vent) to enhance fluid behavior inside the cavity are discussed in this paper. Effect of inserting different plugger speed and inserting vacuum also found in this research study. Found that, the modified design could improve the distribution of velocity and temperature of molten metal inside the mold cavity. The modified design also have optimized the fluid flow and eliminate the vortex formation.